[Image 59] - Smith, Captain Sir William [?ob. 1732] (My University, 1802)
Captain Sir William Smith was in the Royal Engineers.
Original drawings and paintings of Ireland and Scotland, vol 1
Portrait of a remarkable stone at the Giants Causeway by Sir Wm Smith 1802.
Keywords: Architectural drawings; Giant's Causeway (Northern Ireland); Antrim (Northern Ireland : County) -- Pictorial works; Landscapes (Representations) 1800-1810